2020
DOI: 10.3390/foods9040455
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cocoa Butter and Cocoa Butter Equivalent in a Chocolate Confectionery on Human Blood Triglycerides, Glucose and Insulin

Abstract: Given the rising trend in the consumption of chocolate confectioneries, the shortage in cocoa butter (CB) production remains a constant threat to food manufacturers. Therefore, exploring alternative plant sources of CB is essential. Sal fat, obtained from seed kernels of trees, has the potential to substitute CB in chocolate confectioneries. The primary aims of this randomised controlled, crossover trial was to compare the glycaemic, insulinaemic and lipidaemic response of two different oil types (CB and Sal f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…CB, also called theobroma oil, is a light-yellow vegetable fat that comes from the cocoa bean and is responsible for the melting properties of chocolate. As mentioned, cocoa butter (CB) consists mainly of palmitic fatty acids (C16:0), stearic acid (C18:0), oleic acid (C18:1), and linoleic acid (C18:2), with low levels of lauric acid (C12: 0) and myristic acid (C14:0) for cocoa butter and a fatty acid profile of approximately 60% saturated fat, 35% monounsaturated fat, and 1% polyunsaturated fat [ 54 ]. Although saturated fat is generally thought to adversely raise total cholesterol and LDL cholesterol levels, early studies also suggested that stearic acid may be hypo-cholesterolemic [ 55 ].…”
Section: Potential Bioactive Nutrients That May Interfere With Nafldmentioning
confidence: 99%
“…CB, also called theobroma oil, is a light-yellow vegetable fat that comes from the cocoa bean and is responsible for the melting properties of chocolate. As mentioned, cocoa butter (CB) consists mainly of palmitic fatty acids (C16:0), stearic acid (C18:0), oleic acid (C18:1), and linoleic acid (C18:2), with low levels of lauric acid (C12: 0) and myristic acid (C14:0) for cocoa butter and a fatty acid profile of approximately 60% saturated fat, 35% monounsaturated fat, and 1% polyunsaturated fat [ 54 ]. Although saturated fat is generally thought to adversely raise total cholesterol and LDL cholesterol levels, early studies also suggested that stearic acid may be hypo-cholesterolemic [ 55 ].…”
Section: Potential Bioactive Nutrients That May Interfere With Nafldmentioning
confidence: 99%
“…Solid fats also contain saturated fats of which excessive consumption has been associated with elevated cardiovascular disease risk and could lead to other health complications [237]. In contrast, oleogels have been found to reduce postprandial insulinemia and lipidemia [238][239][240][241]. By structuring plant oils into oleogels, plant-based lipids could be made to behave similarly to animal fat, for example, in plant-based meats [242].…”
Section: Formation Of Gelsmentioning
confidence: 99%
“…CB has a melting point ranging from 27°C -35°C. The character of CB depends on its fatty acid composition [9], [17], [27]. CB contains palmitic, stearate, and oleic fatty acids, giving it a cool and melting character in the mouth [9], [17].…”
Section: A Cocoa Butter (Cb)mentioning
confidence: 99%